Effect of vitamin C and vitamin E supplementation on endothelial function: a systematic review and meta-analysis of randomised controlled trials. Issue 8 (31st March 2015) - Ashor, Ammar W.; Siervo, Mario; Lara, Jose; Oggioni, Clio; Afshar, Sorena; Mathers, John C.
Abstract : Randomised controlled trials (RCT) testing the effects of antioxidant supplements on endothelial function (EF) have reported conflicting results. We aimed to investigate the effects of supplementation with antioxidant vitamins C and E on EF and to explore factors that may provide explanations for the inconsistent results. We searched four databases (MEDLINE, Embase, Cochrane Library and Scopus) from inception until May 2014 for RCT involving adult participants aged ≥ 18 years who were supplemented with vitamins C and E alone or in combination for more than 2 weeks and reporting changes in EF measured using flow mediated dilation or forearm blood flow. Data were pooled as standardised mean difference (SMD) and analysed using a random-effects model. Significant improvements in EF were observed in trials supplementing with vitamin C alone (500–2000 mg/d) (SMD: 0·25, 95 % CI 0·02, 0·49, P = 0·043) and vitamin E alone (300–1800 IU/d; 1 IU vitamin E = 0·67 mg natural vitamin E) (SMD: 0·48, 95 % CI 0·23, 0·72, P = 0·0001), whereas co-administration of both vitamins was ineffective (vitamin C: 500–2000 mg/d; vitamin E: 400–1200 IU/d) (SMD: 0·12, 95 % CI − 0·18, 0·42, P = 0·428). The effect of vitamin C supplementation on EF increased significantly with age (β 0·023, 95 % CI 0·001, 0·05, P = 0·042). There was a significant negative correlation between baseline plasma vitamin E concentration and the effect of vitamin E supplementation on EF (β − 0·03, 95 % CI − 0·06, − 0·001, P = 0·029). Supplementation with either vitamin C or vitamin E alone improves EF. However, subgroup analysis emphasises the importance of careful characterisation and selection of a population group which may benefit from such supplementation.